Heritability, Correlation and Path Analysis of Agronomic Characters in M4 Toraja Local Red Rice Mutans - A Reny Batara Sofia; Rinaldi Sjahril; Muhammad Riadi; Rafiuddin Rafiuddin; Trisnawaty A.R.; Nurhaya J Panga (Hasanuddin University, 2023)
Rice is an important commodity for main staple in Indonesia. The need for rice will increase so that efforts are needed to increase its production. The use of superior varieties is an option to optimize land use whose area is increasingly limited due to population growth. The development of varieties is not only considered in terms of food production but is developed as an ingredient to meet nutritional needs. One of the local rice varieties that have the potential to be developed is Toraja local red rice (Pare Lea). Development of local rice character improvement through mutation breeding. Selection of superior genetypes is not only based on high production characters, but also the necessary information related to the relationship between characters that support production. This study aims to obtain information about the relationship between the components of growth and production of Toraja local red rice. This experiment used 9 mutant lines at fourth generation (M4) as treatment and 1 non-mutant line as control. Agronomic characters that can support rice production were such as plant height, panicle length and grain yield per plant